2017
DOI: 10.1631/jzus.b1600442
|View full text |Cite
|
Sign up to set email alerts
|

全麻诱导期经静脉输液管缓慢滴注和快速输注芬太尼对该药诱发呛咳的影响

Abstract: Abstract:Objective: Fentanyl-induced cough (FIC) is a common complication with a reported incidence from 18.0% to 74.4% during general anesthesia induction. FIC increases the intrathoracic pressure and risks of postoperative nausea and vomiting, yet available treatments are limited. This study was designed to investigate whether administering fentanyl via a slow intravenous fluid line can effectively alleviate FIC during induction of total intravenous general anesthesia. Methods: A total number of 1200 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…When the injection time was prolonged to 30 s, the incidence of cough decreased to 1.3% ( Lin et al, 2005 ). Administration of 2 μg⋅kg −1 fentanyl via a slow intravenous fluid line at rate of 0.058 µg⋅kg −1 ∙s −1 during induction reduced the incidence of FIC than via direct injection 9.1% vs. 55.9%, as were the severity grades ( Liu et al, 2017 ). There were no statistical differences between the two groups with regard to other adverse reactions.…”
Section: Influencing Factors Of Fentanyl-induced Coughmentioning
confidence: 99%
“…When the injection time was prolonged to 30 s, the incidence of cough decreased to 1.3% ( Lin et al, 2005 ). Administration of 2 μg⋅kg −1 fentanyl via a slow intravenous fluid line at rate of 0.058 µg⋅kg −1 ∙s −1 during induction reduced the incidence of FIC than via direct injection 9.1% vs. 55.9%, as were the severity grades ( Liu et al, 2017 ). There were no statistical differences between the two groups with regard to other adverse reactions.…”
Section: Influencing Factors Of Fentanyl-induced Coughmentioning
confidence: 99%
“…There are three possible explanations for this inhibitory effect. First, when sufentanil was added to the mechanical dropper, it was diluted by the original liquid present in the dropper, the fluid coming from the infusion bag, and the mixture continuously dropping down to the flow tube [ 17 ]. In this research, the average patient weight in both groups was approximately 60 kg, with an induction dose of sufentanil of 0.3 μg·kg − 1 and an initial concentration of 5 μg·ml − 1 , the average dosage was around 18 μg, and the mean volume was 3.6 ml.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of sample size was based on a 16% reported incidence of SIC following an induction dose of sufentanil of 0.3 μg·kg − 1 [ 9 ]. A previous study reported a reduction of fentanyl-induced cough via mechanical dropper of approximately 84% [ 17 ], so we assumed that this simple method would cause at least an 80% decrease in the incidence of SIC. At α = 0.05 and β = 0.10, we needed to enroll 93 patients in each group; therefore, we recruited 200 patients to account for possible reduction in sample size due to patients dropping out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fentanyl, has vagotonic effects that sometimes result in severe bradycardia, combined with propofol the result is particularly hypotensive 15. Bolus injection for anesthesia induction was not adopted, because blood concentration would rise sharply, and then the side effects of all the drugs are superimposed, leading to unwanted tachycardia and hypotension 1619. Volatile agent for maintaining anesthesia is believed to have pleiotropic effects on protecting against myocardial ischemia, as well as maybe reduce the incidence of intraoperative awareness 6,20,21.…”
Section: Discussionmentioning
confidence: 99%